Regulation of Atrial Fibrosis by the Bone. Issue 2 (February 2019) - Yi, Yi; Du, Lili; Qin, Mu; Chen, Xiao-Qing; Sun, Xue-Nan; Li, Chao; Du, Lin-Juan; Liu, Yuan; Liu, Yan; Sun, Jian-Yong; Tang, Zisheng; Xu, Min; et al.
Abstract : MR (mineralocorticoid receptor) antagonists have been demonstrated to provide beneficial effects on preventing atrial fibrosis. However, the underlying cellular and molecular mechanisms remain unclear. We aim to determine the role of osteoblast MR in atrial fibrosis and to explore the underlying mechanism. Using osteoblast MR knockout mouse in combination with mutant TGF (transforming growth factor)-β1 transgenic mouse, we demonstrated that MR deficiency in osteoblasts significantly attenuated atrial fibrosis. Mechanistically, MR directly regulated expression of OCN (osteocalcin) in osteoblasts. Both carboxylated and undercarboxylated OCNs (ucOC) were less secreted in osteoblast MR knockout mice. Mutant TGF-β1 transgenic mice supplemented with recombinant ucOC showed aggravated atrial fibrosis. In cultured atrial fibroblasts, ucOC treatment promoted proliferation and migration of atrial fibroblasts, whereas cotreatment with an antagonist for a GPRC6A (G-protein–coupled receptor, family C, group 6, member A) abolished these effects. Western blotting analysis revealed upregulation of PKA (protein kinase A) and CREB (cAMP-response element–binding protein) phosphorylation after ucOC treatment. Inhibition of PKA with its antagonist reduced ucOC-induced proliferation and migration of atrial fibroblasts. Finally, the impact of osteoblast MR deficiency on atrial fibrosis was abolished by ucOC administration in mutant TGF-β1 transgenic mice. Taken together, MR deficiency in osteoblasts attenuated atrial fibrosis by downregulation of OCN to promote proliferation and migration of atrial fibroblasts. Abstract : Supplemental Digital Content is available in the text.